75 Can Regionalized Livestock Production and Meat Packing Meet the Food Needs of Today's Consumers?. (8th October 2021) - Apple, Jason
Abstract: Meat shortages in many of the largest retail chains during the early months of the COVID-19 pandemic affected millions of U.S. consumers. In addition, wait times for custom slaughter of meat animals increased from days to weeks to upwards of 14 mon. Interruptions in livestock slaughter and meat supplies have renewed the emphasis on medium, small, and very small meat slaughters/processors. Numerous states are investing in slaughter/processing plant construction, renovation of existing plants, and establishing or reestablishing state inspection programs. It is conceivable that this reinvestment may alleviate some of the meat supply limitations; yet, there are a number of factors these plants need to address for economic sustainability, including (but are not limited to): consistency of local and regional livestock supply; availability of trained, experienced workforce; plant holding pens and slaughter floor design; pre-slaughter animal welfare training and compliance; development and implementation of food safety programs; fresh and frozen storage capacities; local and regional marketing channels and modes of distribution; and by-products markets and offal disposal. Regardless of plant size, the ultimate goal of all meat packers/processors is the production of consistent, readily available and affordable, high-quality meat and meat products; however, the traditional driving forces of price and taste are being slowly supplanted by consumers' concerns about production practices and animal management, perceived nutritional benefits, animal welfare concerns, food locality, and conveniences. This presentation will attempt to amalgamate the challenges facing medium, small, and very small meat processors with consumers' preferences in relation to the sustainability of these revitalized segments of the livestock and meats industry.